Morelloflavone and Molecular Docking from Stembark of Chisocheton lasiocarpus and Its Cytotoxic Activity Against Breast Cancer Mcf-7 Cell Lines - Nurlelasari, Nurlelasari; Harneti, Desi; Maharani, Rani; Darwati, Darwati; Mayanti, Tri; Farabi, Kindi; Hanafi, Muhammad; Supratman, Unang (Molekul, 2023)
Chisocheton is a plant of the Meliaceae family which has been known as a source of limonoids, triterpenoids, steroids, alkaloids and phenolics. This plant is the second largest in the Meliaceae, with 53 species widely distributed in tropical and subtropical regions including Indonesia. From this genus, compounds that have interesting activities have been found, including anti-inflammatory, antimalarial, cytotoxic, antitumor and anticancer. One of the species that has the potential to find new compounds is Chisocheton lasiocarpus because there are still few phytochemical studies. This study aims to inform the structural elucidation of one of the compounds from the stem bark of C. lasiocarpus, namely morelloflavone and its cytotoxic potential against breast cancer cells using the in silico method against ER-α receptors (PDB code: 3ERD), ER-β (PDB code: 1QKM). ) and HER-2 (GDP code: 3PP0).